2013
DOI: 10.1007/s00540-013-1566-z
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic study of sevoflurane-based general anesthesia on cognitive function in children

Abstract: These findings from our self-controlled study show that sevoflurane-based general anesthesia does not have significantly adverse effects on the cognitive function of 4- to 7-year-old children at 1 month and 6 months after strabismus surgery. Additional studies with a larger sample size are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 26 publications
0
18
1
1
Order By: Relevance
“…In contrast to our results and the above-mentioned studies, Kayaalp et al [26] reported that repeated general anesthesia does not seem to disturb the child's psychological health further when proper perioperative management is undertaken, such as the use of proper premedication, effective postoperative pain control, having good rapport with children, and performing the surgery and anesthesia on an outpatient basis, where possible [26]. Fan et al [27] have another opinion that sevoflurane-based general anesthesia does not have significant adverse effects on the attention and other cognitive functions in children between the ages of 4 and 7 years when evaluated at 1 month and 6 months after exposure to general anesthesia. Also, Cans [28] cited that most pediatric general anesthesia studies were observational studies, showing a very mild adverse effect on cognitive functions.…”
Section: Discussioncontrasting
confidence: 76%
“…In contrast to our results and the above-mentioned studies, Kayaalp et al [26] reported that repeated general anesthesia does not seem to disturb the child's psychological health further when proper perioperative management is undertaken, such as the use of proper premedication, effective postoperative pain control, having good rapport with children, and performing the surgery and anesthesia on an outpatient basis, where possible [26]. Fan et al [27] have another opinion that sevoflurane-based general anesthesia does not have significant adverse effects on the attention and other cognitive functions in children between the ages of 4 and 7 years when evaluated at 1 month and 6 months after exposure to general anesthesia. Also, Cans [28] cited that most pediatric general anesthesia studies were observational studies, showing a very mild adverse effect on cognitive functions.…”
Section: Discussioncontrasting
confidence: 76%
“…A variety of clinical studies have been performed evaluating the association between anesthesia exposure and long-term cognitive deficits, but the ages of anesthesia exposure have been variable, ranging from exposure in children as early as age 1 to as late as age 7. [12][13][14][15][16][17][18][19][20][21][22] No study to date has specifically evaluated the association between various ages of initial anesthesia exposure and neurodevelopmental deficit.…”
mentioning
confidence: 98%
“…Retrospective clinical studies were relatively inconclusive, with some, but not all studies, supporting findings of cognitive changes after early childhood exposure to anesthesia (Andropoulos et al, 2014; Bartels et al, 2009; DiMaggio et al, 2009; Fan et al, 2013; Flick et al, 2011; Graham et al, 2016; Ing et al, 2012; Kalkman et al, 2009; O’Leary et al, 2016; Sprung et al, 2009; Sun et al, 2016; Wilder et al, 2009) (See Figure 4, A Timeline - 15 Years of Anesthetic Neurotoxicity). This debate has prompted a few, rigorously designed clinical trials, many of which are just now starting to publish their results.…”
Section: Discussionmentioning
confidence: 99%